Towards optimal adsorption heat transformers for heat upgrading: Learnings from a validated full-scale model - Engelpracht, Mirko; Rezo, Daniel; Postweiler, Patrik; Lache, Marten; Henninger, Matthias; Seiler, Jan; Bardow, André (Applied thermal engineering, 2024)
Adsorption heat transformers (AdHTs) have recently been proposed to decarbonize industrial heat supply by upgrading low-temperature waste heat to higher temperatures. An AdHT’s performance strongly depends on equilibrium and kinetic properties of the selected working pair, component and cycle designs, operating temperatures, volume flow rates, and phase times. Exploring this multi-dimensional design space requires a validated full-scale dynamic AdHT model. Due to the lack of such a model, the optimal design and achievable performance of AdHTs are unknown. Here, we address this gap in two steps: First, we developed, calibrated, and validated a dynamic AdHT model for our one-bed prototype, which uses silica gel 123 & water. The model accurately predicted thermal efficiency and power density, with average deviations below 8.1% from measurements. Second, we successively optimized the process design for heat upgrading from 90 to 110 °C and releasing condensation heat at 25 °C. Improvements in the component designs increased the maximal thermal efficiency by 117 % to 0.35 J(th)J(th)−1 (43 % of the maximal Carnot efficiency) and the maximal power density by 79 % to 304 Wkg−1. Vapor mass recovery increased thermal efficiency the most. Combined heat and vapor mass recovery increased power density the most. The resulting AdHT also achieved an electrical efficiency of up to 40 J(th)J(el)−1. Thus, an AdHT can compete with a high-temperature heat pump from a thermodynamic perspective, encouraging further research into AdHTs. [Display omitted] •First full-scale dynamic model of an adsorption heat transformer (AdHT).•Efficiency COP and power density SHP are predicted with 8.1% deviation.•High performance requires casings tightly fit to the heat exchangers.•Power density SHP improves by combined heat and vapor mass recovery.•Optimal AdHT designs can exceed the efficiency EER of high-temperature heat pumps.